In the image and likeness of the nobles: the case of the new neighbours of the city of Caloto, Popayan province, Kingdom of New Granada, 1784-1800 (2022)
The arrival of the Bourbons to the Hispanic Monarchy brought with it new ways of conceiving of the society attached to its body politic. New laws and rights were promoted, which motivated among the free population a recognition of their status andstates in the space of the localities of Hispanic America. In this sense, the present work attempts to approach the case of the integration and recognition of the free population of the city of Caloto, And the contiguous seat of Quilichao. The analysis of the census carried out in the year 1784 in Caloto and of the decompiled documentation of the General Archive of the Nation, from the colony section (Cauca populations) allows the observation and identification that in the framework of the interwoven relationships of the free or mestizo population there were some activities that influenced incorporation and the forms of participation in the community.